2020
DOI: 10.3390/cells9081897
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JNK1 in Neuronal Polarization During Brain Development

Abstract: The c-Jun N-terminal Kinases (JNKs) are a group of regulatory elements responsible for the control of a wide array of functions within the cell. In the central nervous system (CNS), JNKs are involved in neuronal polarization, starting from the cell division of neural stem cells and ending with their final positioning when migrating and maturing. This review will focus mostly on isoform JNK1, the foremost contributor of total JNK activity in the CNS. Throughout the text, research from multiple groups will be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 145 publications
(208 reference statements)
1
10
0
Order By: Relevance
“…The alterations detected in the dendritic projections of immature hippocampal neurons and mature cortical neurons of Mkk4 ∆/∆ and Mkk7 ∆/∆ mice support that the MKK4/MKK7-JNK signaling pathway has a role in the maintenance of the dendritic and axonal processes [35] in accordance with Bjorkblom et al, who found that JNK phosphorylation of MAP2 plays an important role in defining dendritic architecture in the brain [36].…”
Section: The Deletion Of Mkk4 and Mkk7 Gene Alters Immature Hippocampal Neuronssupporting
confidence: 87%
“…The alterations detected in the dendritic projections of immature hippocampal neurons and mature cortical neurons of Mkk4 ∆/∆ and Mkk7 ∆/∆ mice support that the MKK4/MKK7-JNK signaling pathway has a role in the maintenance of the dendritic and axonal processes [35] in accordance with Bjorkblom et al, who found that JNK phosphorylation of MAP2 plays an important role in defining dendritic architecture in the brain [36].…”
Section: The Deletion Of Mkk4 and Mkk7 Gene Alters Immature Hippocampal Neuronssupporting
confidence: 87%
“…This network converges on the SIGNOR pathways for mitochondrial biogenesis and inflammation, and this is consistent with prior evidence linking mitochondrial dysfunction [ 44 , 45 , 46 , 47 , 48 , 49 ] and neuroinflammation [ 50 , 51 , 52 ] to ASD. The polarization and proliferation pathways are essential regulators of neural stem cell self-renewal and differentiation [ 53 , 54 , 55 ], while the apoptosis and cell death signalling pathways are implicated as mechanisms whereby microglia drive synaptic pruning, and the maturation and migration of neuronal progenitors [ 56 ]. In addition, this subset of proteins was significantly enriched for five ClinVar disease pathways associated with neuropathology, mitochondrial dysfunction or auto-immune disease ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…While, studies also showed that blocking the JUN could prevent the degradation and apoptosis of chondrocytes [21], and the inhibition of JUN transcriptional activity protects against osteoarthritis cartilage destruction [22]. Moreover, studies also showed that JUN could participate in the regulation of antioxidant responses in neurons [23] and may have the potential of regulating the peripheral myelin development [24] and neuronal polarization during brain development [25].…”
Section: Discussionmentioning
confidence: 99%